Association between physical activity levels and polypharmacy in hypertensive patients - Bueno, Denise R.; Monteiro, Henrique L.; Rosa, Clara S. C.; Codogno, Jamile S.; Fernandes, Rômulo A.; Marucci, Maria F. N. (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2016)
Background: exercise reduces medication usage in hypertensive people. However, different domains of physical activity (PA) have not been studied in order to analyze their relationship with the use of multiple medications, known as polypharmacy. Purpose: To examine the association between PA in different domains (leisure-Time, locomotion and occupational) and polypharmacy in hypertensive patients. Methods: This is a cross-sectional study carried out with 190 hypertensive patients. Polypharmacy was defined as simultaneous use of three or more drugs. The PA domains were the independent variables: Locomotion PA (LPA), Leisure Time PA (LTPA) and Occupational PA (OPA). The multiple logistic regression was performed to analyze the associations. The Mann Whitney test determined whether medications usage differ according to each domain of PA. Results: The total number of drugs used ranged from 0 to 7, which represents an average of 2.35 (±1.6) drugs per person. Scores of LTPA (OR: 3.25; CI95%:1.61-6.54) and LPA (OR: 2.15; CI95%:1.09-4.25) were inversely associated with polypharmacy in hypertensive patients, in the multiple logistic regression analysis (controlled by BMI, chronic diseases, smoking, alcohol consumption and skin color). Conclusions: lower PA in leisure time and locomotion were associated with polypharmacy in hypertensive people.
Keywords: Hypertension; Hysical activity; Polypharmacy